Credit ratings and the standardised approach to credit risk in Basel II - Patrick Van Roy (European Central Bank (ECB), 2005)
This paper simulates the minimum capital requirements for the wholesale exposures of a medium-sized bank in each EMU country depending on the credit rating agencies chosen by the bank to risk-weight its exposures in the standardised approach to credit risk in Basel II. Three main results emerge from the analysis. First, although the use of different combinations of credit rating agencies leads to significant differences in minimum capital requirements, these differences never exceed 10% of EMU banks' regulatory capital for wholesale exposures on average. Second, the standardised approach provides a small regulatory capital incentive for banks to use several credit rating agencies to risk-weight their exposures. Third, the minimum capital requirements for the wholesale exposures of EMU banks will be higher in Basel II than in Basel I. I also show that the incentive for banks to engage in regulatory arbitrage in the standardised approach to credit risk is limited.
Keywords: G21; G28; 330; capital requirements; credit rating agencies; New Basel Capital Accord; Basler Akkord; Kreditrisiko; Kreditwürdigkeit; Monte-Carlo-Simulation; Basler Akkord